Seroprevalence of mycoplasmosis in poultry of Bhaktapur - Khanal, Doj Raj; Ranjit, Eliza; Adhikari, Sanjeev Kumar; Ghemosu, Bimal; Prajapati, Meera; Shrestha, Swoyam Prakash (International Journal of Applied Sciences and Biotechnology, 2018)
Mycoplasmas are amongst the avian pathogens that causes chronic respiratory and joint diseases incurring a huge economic loss to poultry industry of Nepal. Among different species of Mycoplasmas, we investigate Mycoplasma gallisepticum-synoviae from the serum samples of the poultry using Enzyme Linked Immuno Sorbent Assay (ELISA) and dot-ELISA test of ImmunoComb. These tests rely on the antibodies present in the serum samples which binds to the pre-coated antigen in the ELISA/developing plates. A total of 92 sera samples were collected, of which 62 were from broiler and 30 were from layers. Of the 92 samples taken from different farms of Bhaktapur in early 2017, thirty (32.6%) were found positive on standard or routine ELISA and fifty-four (58.7%) on dot-ELISA. It further indicates high rate of infections in broiler (42 on dot-ELISA and 24 on standard ELISA) than in layers (12 in dot-ELISA and 6 on standard ELISA) to M. gallisepticum and M. synoviae. The present result indicates higher efficacy of dot-ELISA over standard one as the latter could not efficiently detect the infections as compared to the dot-ELISA. Furthermore, this finding poses an alarming threat to the commercial poultry industries of Nepal where there is lack of effective biosecurity practices and preventive vaccination policy. Int. J. Appl. Sci. Biotechnol. Vol 6(1): 23-26